Early Islamic legal theory : the Risāla of Muḥammad ibn Idrīs al-Shāfiʻī - Lowry, Joseph E. (Studies in Islamic Law and Society, 2007)
The Risāla of al-Shāfiʿī (d. 204/820), the earliest preserved work of Islamic legal theory, has been understood in previous scholarship as either the elaboration of a hierarchy of sources of law (Qurʾān, Sunna, consensus, and analogical reasoning) or an extended defense of the Sunna. Through a careful rereading of this celebrated text, this book offers a comprehensive reinterpretation of the Risāla , in which Shāfiʿī formulated an all-encompassing hermeneutic that portrays the law as a tightly interlocking structure organized around defined interactions of the Qurʾān and the Sunna. Topics covered include Shāfiʿī's creative account of the law's architectonics, hermeneutical techniques, legal epistemology, relationship to kalām , and the role of consensus ( ijmāʿ ).